Desorption atmospheric pressure photoionization high‐resolution mass spectrometry: a complementary approach for the chemical analysis of atmospheric aerosols. (21st May 2015) - Parshintsev, Jevgeni; Vaikkinen, Anu; Lipponen, Katriina; Vrkoslav, Vladimir; Cvačka, Josef; Kostiainen, Risto; Kotiaho, Tapio; Hartonen, Kari; Riekkola, Marja‐Liisa; Kauppila, Tiina J.
Abstract : Rationale: On‐line chemical characterization methods of atmospheric aerosols are essential to increase our understanding of physicochemical processes in the atmosphere, and to study biosphere‐atmosphere interactions. Several techniques, including aerosol mass spectrometry, are nowadays available, but they all suffer from some disadvantages. In this research, desorption atmospheric pressure photoionization high‐resolution (Orbitrap) mass spectrometry (DAPPI‐HRMS) is introduced as a complementary technique for the fast analysis of aerosol chemical composition without the need for sample preparation. Methods: Atmospheric aerosols from city air were collected on a filter, desorbed in a DAPPI source with a hot stream of toluene and nitrogen, and ionized using a vacuum ultraviolet lamp at atmospheric pressure. To study the applicability of the technique for ambient aerosol analysis, several samples were collected onto filters and analyzed, with the focus being on selected organic acids. To compare the DAPPI‐HRMS data with results obtained by an established method, each filter sample was divided into two equal parts, and the second half of the filter was extracted and analyzed by liquid chromatography/mass spectrometry (LC/MS). Results: The DAPPI results agreed with the measured aerosol particle number. In addition to the targeted acids, the LC/MS and DAPPI‐HRMS methods were found to detect different compounds, thus providing complementary information about the aerosol samples. Conclusions: DAPPI‐HRMS showed several important oxidation products of terpenes, and numerous compounds were tentatively identified. Thanks to the soft ionization, high mass resolution, fast analysis, simplicity and on‐line applicability, the proposed methodology has high potential in the field of atmospheric research. Copyright © 2015 John Wiley & Sons, Ltd.